Measurement of mass attenuation coefficient of ZIRCONIUM (Zr), Zirconium Chloride (ZrCl4) and Zirconium Silicate (ZrSiO4) near the K-edge using synchrotron radiation. (2021) - Mahesh Kumar, A.; Manjula, G.; Nageshwar Rao, A.S.
Abstract: The experimental work describes the measurement of the mass attenuation coefficient of zirconium (Zr) and zirconium compounds such as ZrCl4 and ZrSiO4 near the K-edge region in the range of 17919–18664 eV using the EXAFS beam line (BL-09) Synchrotron Radiation Source at the Raja Ramanna Center for Advanced Technology (RRCAT) Indore. The result reflects the data of X-ray mass attenuation coefficient for Zr, ZrCl4, and ZrSiO4 in the K-edge XAFS region and the results are compared to the standard theoretical values obtained from NIST XCOM. Just close to the K-edge it was found that the highest deviation with an oscillatory aspect and decreases as it moves away from the edge of the absorption. This oscillatory structure exists just above the observed absorption edge, i.e. 18 keV, and is limited to 200–250 eV above the K-edge.